REPRESENTATION OF THE LINGUISTIC WORLDVIEW THROUGH TABOO WORDS - Olimova Dilafruzxon Baxtiyorjon qizi (Western European Studies, 2026)
This research aims at comprehensively studying the natural and cultural aspects of taboo words in Uzbek language. Various sources were analyzed, classification principles developed, and social-psychological, ethnocultural, and linguistic factors highlighted with regard to their nature, usage scope, and cultural implications. The study concluded that taboo words are not only integral components of the Uzbek language but also pillars of culture.
Keywords: taboo words; culture; psychology; literary language